Business model innovation and owner–managers: the moderating role of competition. (29th October 2014) - Velu, Chander; Jacob, Arun
Abstract : This study examines the relationship among owner–managers, business model innovation, and competition. We present a newly constructed dataset of 111 new firms that launched electronic trading platforms (business model innovations) in the US and European bond markets between 1995 and 2004. We contribute to the emerging literature on business model innovation by integrating effectuation theory with the Austrian school's view of competition as a discovery process to examine the role of the entrepreneur in business model design. Our findings reveal that the presence of entrepreneurs as owner–managers positively influences the degree of innovation: this relationship is stronger in less competitive environments but is weaker (and may even reverse) in highly competitive environments. We discuss implications for theory and for entrepreneurs in influencing the degree of business model innovation, and suggest future directions for research.